(3TQM ehRhf GdejRGfs - (3EHQGgje Hf MSGes; (3TQjaj , EHQGgje Hf MSGe GdOjf GdcQejGfj,J (B1016 (3g` s
(3ChdgG (B:s
(3hHYO aEf ddYde QjGVkG hMjGVkG hGafGfkG hZjGVkG hWQGFb hTYGHkG s
(3BNQgG (B:s
(3hLGOdge HGdJi gi CMSf hGdehYXI GdMSfI Edi GdNWGHI hGdLOGd Edi GdLOd s
(3GdfSNI HgG MhGTs
(3YdjgG Jedc hhbas
(3hLO HGdCUd Cf GdUaMGJ ef (B93 - 100 (3HjVGA s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdadSaI hGdefWbs